PROFIL KETERAMPILAN KREATIVITAS SISWA SMP NEGERI 1 BANYUDONO PADA MATA PELAJARAN INFORMATIKA - Setyaningsih Setyaningsih (KOLONI, 2023)
One of the most important skills for facing the 21st century is creativity. Based on the results of the Global Creativity Index, Indonesia is ranked under the creative and innovative index. Seeing these results, it is necessary to emphasize that creative skills must be improved so that students are ready to face the era of the industrial revolution 4.0. This study aimed to analyze the initial profile of students' creativity skills at SMP Negeri 1 Banyudono in informatics subject. This research was a qualitative descriptive study with the observation method on students' creative skills. The subjects of this study were 34 students at SMP Negeri 1 Banyudono who were selected using a purposive sampling technique. The results showed that the percentage of attainment of creativity skills was measured using 3 aspects of skills namely Think Creatively were 40.5 %, Work Creatively with Others were 29.7% and Implement Innovations were 24.8%. Keywords: Informatics, Creativity Skills, Initial Profile